HOVON110/ReBeL Study: Results of the Phase I Part of a Randomized Phase I/II Study of Lenalidomide, Rituximab With or Without Bendamustine in Patients With Relapsed/Refractory Follicular Lymphoma. Issue 1 (February 2020) - Stevens, Wendy B.C.; Bakunina, Katerina; Cuijpers, Marloes; Chamuleau, Martine; Beeker, Aart; Fijnheer, Rob; Hebart, Holger; Visser, Hein P.J.; Doorduijn, Jeanette K.; Linton, Kim; Dreyling, Martin; de Jong, Daphne; et al.
Abstract : Supplemental Digital Content is available in the text